“Dentro da barriga da minha mãe eu bebia vegetal”: a vivência das crianças no mundo de Hoasca - Peregrino, Ivana Silva Bastos (2023)
The scientific view of a child it’s going through substantial epistemological changes since the beginning of the twentieth century. By the 1970s and the 1980s, the critical debates took place and starts questioning methods and ethics, as well as epistemological issues. Despite the growth of research on this area, children remain with little scientific visibility if it compares with adult-centered themes. In anthropological and sociological studies, the invisibility of children is greater when it comes to religious contexts and their sociability. This investigation seeks to observe kids that attend a temple, also called “núcleo”, of the Centro Espírita Beneficente União do Vegetal – a Christian and reincarnationist religion. In the ritual, the members of this Brazilian religion drink a psychoactive tea, called “Hoasca” or “vegetal”. The main goal is to understand the social and ritual place of the children in União do Vegetal (UDV). This research is based on the process of religious socialization at Núcleo Conselheiro Salomão Gabriel, in the city of João Pessoa-PB. It follows the experiences of the children’s group. It verifies the activities developed with the group and examines how the children are included and how they react to the rituals. The hoasqueiras children, as they are named in this research, have access to the religious space accompanying their parents. However, the presence of the kids in the environment goes beyond religiosity since it has proved an important social interaction space, with friendship bonds, child’s plays and contact with nature. The analysis is made through the emic perspective. Regarding theoretical-methodological aspects, this is qualitative research. The techniques of semi-structured interviews predominate, mainly with children, but including adults, and participant observation as well. The age group of the main collaborators is between four and eleven years old and the group is composed by thirteen girls and boys. Drawings have also been an important tool to collect data among children. The results show a religious practice centered on the family and hierarchy, without child occupation in it. Although the kids have no role in the rituals, the religion is very open to them. They have an active participation. Even if they cannot participate in all the sessions, they can be present in some rituals. The adults are guided to help the kids when they want to drink the tea ritualistically, and the adults also must acknowledge and consider the children will. The socialization is a two-way street, the children insert themselves and are inserted into religious practice. Both the perception of religiosity and the socialization are evidenced by the triad pairs, child’s plays and nature. The experience of the children’s group among peers differs in the UDV due to this direct connection with the natural world. It has relevance both in the social and religion life since nature is considered sacred.